Prevention of media inspired copycat crime in Malaysia: A legal analysis / Muhammad Arif Azmi … [et al.] - Azmi, Muhammad Arif; Saiful Madzi, Shireen Munira; Yusof, Zulhazmi; M. Yusoff, Muhammad Azzamudeen (2014)
Currently the media is able to flood the minds of the public in general with violent programs that not only show crimes being conducted, but also methods to conduct such crimes. The problem seen here is that certain groups of people which we shall group as the "vulnerable group" are exposed to these programs and have a tendency to mimic the acts. When the crimes are copied from other criminal acts, it is called copycat crimes. The media involved cannot be liable in any way for the violent crimes committed by these individuals. Our aim is to propose amendments to the laws present in Malaysia to prevent these copycat crimes to exist. However, there is also a need to study this subject matter in order to better understand to what extent these violent programs can or have influenced these vulnerable groups and to identify the various ways in which it can be prevented or avoided. In Malaysia, although some scenes that have sex or obscene scenes in the programs televised are usually filtered out especially by the Film Censorship Board of Malaysia or Lembaga Penapisan Filem (LPF) under the Film Censorship Act, with the existence of the internet, the unprocessed films and television programs abroad reach Malaysian shore wirelessly. We believe that there needs to be protection from mediums that can allow unsolicited television programs or film to be viewed.